Resistance to sap-sucking insects in modern-day agriculture - De Vos, Martin; VanDoorn, Arjen (Frontiers in Plant Science, 2013)
Plants and herbivores have co-evolved in their natural habitats for about 350 million years, but since the domestication of crops, plant resistance against insects has taken a different turn. With the onset of monoculture-driven modern agriculture, selective pressure on insects to overcome resistances has dramatically increased. Therefore plant breeders have resorted to high-tech tools to continuously create new insect-resistant crops. Efforts in the past 30 years have resulted in elucidation of mechanisms of many effective plant defenses against insect herbivores. Here, we critically appraise these efforts and – with a focus on sap-sucking insects – discuss how these findings have contributed to herbivore-resistant crops. Moreover, in this review we try to assess where future challenges and opportunities lay ahead. Of particular importance will be a mandatory reduction in systemic pesticide usage and thus a greater reliance on alternative methods, such as improved plant genetics for plant resistance to insect herbivores.